Introduction to drug disposition and pharmacokinetics - Curry, Stephen H.; Whelpton, Robin (Chichester, West Sussex : Wiley, 2017)
'The application of knowledge of drug disposition, and skills in pharmacokinetics, are crucial to the development of new drugs and to a better understanding of how to achieve maximum benefit from existing ones. The book takes the reader from basic concepts to a point where those who wish to will be able to perform pharmacokinetic calculations and be ready to read more advanced texts and research papers. The book will be of benefit to students of medicine, pharmacy, pharmacology, biomedical sciences and veterinary science, including those who have elected to study the topic in more detail, such as via electives and special study modules. It will be of benefit to those involved in drug discovery and development, pharmaceutical and medicinal chemists, as well as budding toxicologists and forensic scientists who require the appropriate knowledge to interpret their findings and as an introductory text for clinical pharmacologists. Early chapters describe the basic principles of the topic while the later ones illustrate the application of those principles to modern approaches to drug development and clinical use. Full colour illustrations facilitate the learning experience and supporting material for course leaders and students can be found on the Companion Web Site'--
'The book takes the reader from basic concepts to a point where those who wish to will be able to perform pharmacokinetic calculations and be ready to read more advanced texts and research papers'--
Drug Administration and Distribution -- Drug Metabolism and Excretion -- Single-compartment Pharmacokinetic Models -- Multiple-compartment and Non-compartment Pharmacokinetic Models -- Kinetics of Metabolism and Excretion -- Clearance, Protein Binding and Physiological Modelling -- Quantitative Pharmacological Relationships -- Pharmacokinetics of Large Molecules -- Pharmacogenetics and Pharmacogenomics -- Additional Factors Affecting Plasma Concentrations -- Effects of Age and Disease on Drug Disposition -- Drug Interactions and Toxicity -- Perspectives and Prospects -- Appendix 1: Mathematical Concepts and the Trapezoidal Method -- Appendix 2: Dye Models to Teach Pharmacokinetics -- Appendix 3: Curve Fitting -- Appendix 4: Pharmacokinetic Simulations.
Includes bibliographical references and index.
Print version record.
Keywords: Pharmacokinetics; Drugs -- Metabolism; Pharmaceutical chemistry; SCIENCE / Chemistry / Organic; Drugs -- Metabolism; Pharmaceutical chemistry; Pharmacokinetics; MEDICAL / Pharmacology; Electronic books; Electronic books